2019
DOI: 10.1111/ssqu.12639
|View full text |Cite
|
Sign up to set email alerts
|

Representation's Effect on Latinx College Graduation Rates*

Abstract: Objective. College enrollments among Latinx students have increased by 12 percent in the last 14 years, but the group's overall graduation rate has only increased by 5 percent, leading researchers to reevaluate the predictors of completion for Latinx students. This study explores the relationship between Latinx graduation rates and various forms of representation. Methods. Random effect modeling using institutional-level data collected from the Integrated Postsecondary Education Data System, 2008-2011, is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Research by Capers (2019) indicated a positive correlation between Latinx faculty representation and increased graduation rates. Academic success and retention could also equal the need for faculty and administration of Color (Capers, 2019;Rodriguez et al, 2016).…”
Section: The Latinx Studentmentioning
confidence: 99%
See 3 more Smart Citations
“…Research by Capers (2019) indicated a positive correlation between Latinx faculty representation and increased graduation rates. Academic success and retention could also equal the need for faculty and administration of Color (Capers, 2019;Rodriguez et al, 2016).…”
Section: The Latinx Studentmentioning
confidence: 99%
“…Research by Capers (2019) indicated a positive correlation between Latinx faculty representation and increased graduation rates. Academic success and retention could also equal the need for faculty and administration of Color (Capers, 2019;Rodriguez et al, 2016). In using data from 2002, Zerquera and Gross's research (2017) noted a direct correlation between the proportion of faculty of color on campus to the success of students of color on campus, including the attainment of baccalaureate degrees.…”
Section: The Latinx Studentmentioning
confidence: 99%
See 2 more Smart Citations
“…For youth from minority communities, structural oppression and lack of representation in higher education settings (Capers, 2019), differential access to physical and behavioral healthcare (Jemigan et al, 2015), and systemic barriers in economic wellbeing (Gibson et al, 2021) can exacerbate difficulties related to a successful emergence into adulthood. The Annie E. Casey Foundation (2018) further found that African American, Indigenous, and Hispanic youth, in particular, who age out of foster care, also fare much worse than their White counterparts exiting foster care, in the areas of education, access to healthcare, and economic wellbeing.…”
mentioning
confidence: 99%